The Role of Exercise to Improve Physiological, Physical and Psychological Health Outcome in Idiopathic Inflammatory Myopathies (IIM) - Lodin K; Espinosa-Ortega F; Lundberg IE; Alexanderson H (Dove Medical Press, 2024)
Karin Lodin,1,2,* Fabricio Espinosa-Ortega,1,2,* Ingrid E Lundberg,1,2 Helene Alexanderson1,3 1Division of Rheumatology, Department of Medicine Solna, Karolinska Institutet, Stockholm, Sweden; 2Department of Gastro, Dermatology and Rheumatology, Theme Inflammation and Aging, Karolinska University Hospital, Stockholm, Sweden; 3Medical Unit Allied Health Professionals, Theme Women's Health and Health Professionals, Karolinska University Hospital, Stockholm, Sweden*These authors contributed equally to this workCorrespondence: Helene Alexanderson, Medical Unit Occupational Therapy and Physical Therapy, Theme Women's Health and Health Professionals, Karolinska University Hospital, Gävlegatan 55, NB02:00, Stockholm, 17176, Sweden, Email helene.alexanderson@ki.seAbstract: Idiopathic inflammatory myopathies (IIM) impact all aspects of health, physiological, physical, and psychological. Hallmark symptoms of IIM are muscle weakness, reduced muscle endurance and aerobic capacity. Recently, pain and fatigue as well as anxiety and depression have emerged as common and debilitating symptoms in patients with IIM. The aim of this scoping review is to, in a holistic way, describe how IIM impact patients' physiological, physical, and psychological health and how exercise has a role to treat as well as potentially counteract the effects of the disease. Inflammation induces non-immune response and organ damage. These changes with additional impact of physical inactivity lead to muscle impairment and reduced aerobic capacity. Pain, fatigue and low psychological well-being and overall quality of life are also common health aspects of IIM. Medical treatment can reduce inflammation but has in turn serious side effects such as muscle atrophy, type-II diabetes, and hypertension, which exercise has the potential to treat, and perhaps also counteract. In addition, exercise improves muscle function, aerobic capacity and might also reduce fatigue and pain. New evidence shows that reducing systemic inflammation may also improve patient-reported subjective health, quality of life and psychological well-being. Exercise in combination with medical treatment is becoming an important part of the treatment for patients with IIM as exercise has the potential to promote health aspects of various dimensions in patients with IIM.Keywords: exercise, idiopathic inflammatory myopathies, treatment